Antibacterial Activity of Some Biologically Active: Analogues of Phthalein Dyes - Kukreti, V.; Chamoli, R.P. (Asian Journal of Chemistry, 2010)
A new series of biologically active phthalides has been synthesised and tested for their antibacterial activity against the bacteria S. aureus and E. coli. Some of them have shown significant activity.